Influence of teacher pedagogical skills and attendance on students' academic performance - Arthur, Saraswati; Imoro, Abdul Rahim (Journal of Social, Humanity, and Education, 2025)
Purpose: The study examined the impact of teacher pedagogical skills and teacher attendance on students' foundational literacy and numeracy performance in eight sampled basic schools across four districts in Northern Ghana. Methodology/approach: Using a mixed-methods approach, a total of 216 school visits were conducted, with 120 lessons observed. Results/findings: Results from the study revealed that most teachers in the Kumbungu district were rated either distinguishable or proficient, and the majority in Nanton, Savelugu, and Tolon were rated proficient. The mean scores showed that teachers in Tolon were lagging in some pedagogical skills. Regression analyses revealed that both teacher attendance and teacher pedagogical skills were significant determinants of students’ academic performance, especially in facilitating learners to achieve excellent grades. The qualitative findings also revealed that teacher attendance influenced students’ academic performance and attendance, which may eventually lead to a high rate of school dropout in the long run. Conclusion: Teacher attendance and teacher pedagogical skills play significant roles in student academic performance in literacy and numeracy even though there may be other contributing factors. Essentially, all stakeholders in education should adopt holistic approaches in addressing identified obstacles to improving learning outcomes. Limitations: The study considered only grades 1 to 3 teachers in eight schools and hence extending to other grades in these schools could have revealed diverse findings. Contribution: The study advances knowledge on the impact of teachers’ pedagogical skills and attendance on the academic performance of students and also inform policy makers to implement policies to address associated challenges.